Major Challenges for African Women Theologians in Theological Education (1989–2008) - Phiri, Isabel Apawo (International Review of Mission, 2009)
The paper reflects on the major challenges for African women theologians in theological education as presented and experienced in the Circle of Concerned African Women Theologians (“Circle”) which was launched in Ghana in 1989 as a community of African women theologians who come together to reflect on what it means to them to be women of faith within their experiences of religion, culture, politics and social-economic structures in Africa. Four major challenges are identified that African women theologians have had to contend with and which are still present, namely (1) re-defining the identity of African women theologians; (2) promoting more women to study theology and be on permanent staff; (3) inclusion of African women's theology in the theological curriculum; and (4) collaboration with male theologians.
free